1996
DOI: 10.1148/radiology.200.2.8685335
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic aortic injury: diagnosis with contrast-enhanced thoracic CT--five-year experience at a major trauma center.

Abstract: The CT finding of mediastinal hemorrhage alone is sensitive for traumatic aortic injury, but the finding of aortic injury is more specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(73 citation statements)
references
References 0 publications
2
69
1
1
Order By: Relevance
“…Although some studies supported the use of CT scan in highrisk patients, many others were critical and reported poor results. In a meta-analysis of 18 studies in the Englishlanguage literature for 1983 through 1995, Mirvis et al 12 reported a sensitivity of 97.0% for aortic injury and 99.3% for mediastinal hemorrhage and a specificity of 99.8% and 87.1%, respectively. The authors suggested that all patients with a mechanism of injury suggestive of aortic injury should undergo a chest CT evaluation and supplementary angiographic evaluation should be reserved only for patients with CT findings of periaortic, middle, or superior mediastinal hemorrhage.…”
Section: Methodsmentioning
confidence: 99%
“…Although some studies supported the use of CT scan in highrisk patients, many others were critical and reported poor results. In a meta-analysis of 18 studies in the Englishlanguage literature for 1983 through 1995, Mirvis et al 12 reported a sensitivity of 97.0% for aortic injury and 99.3% for mediastinal hemorrhage and a specificity of 99.8% and 87.1%, respectively. The authors suggested that all patients with a mechanism of injury suggestive of aortic injury should undergo a chest CT evaluation and supplementary angiographic evaluation should be reserved only for patients with CT findings of periaortic, middle, or superior mediastinal hemorrhage.…”
Section: Methodsmentioning
confidence: 99%
“…Aortography re mains the gold standard, although a role for en hanced CT has been reported [1,2]. CT is highly specificfor the detectionof traumatic aortic injuries in the presence of one or more signs of vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…CT is highly specificfor the detectionof traumatic aortic injuries in the presence of one or more signs of vascular injury. Negative CT findings have nearly a 100% negativepredictive value [1,2]. Transesophageal echocardiography or CT has beenrecommendedfor initial imaging in suspected aortic transection [1,3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidetector computed tomography (MDCT) has been shown to be accurate in noninvasively assessing these disorders [6][7][8]. The optimal CT imaging technique to be used for traumatic aortic injury and aortic dissection is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%